Emulation for Digital Preservation in Practice: The Results - Jeffrey van der Hoeven; Bram Lohman; Remco Verdegem (International Journal of Digital Curation, 2007)
In recent years a lot of research has been undertaken to ascertain the most suitable preservation approach. For a long time migration was seen as the only viable approach, whereas emulation was looked upon with scepticism due to its technical complexity and initial costs. In 2004, the National Library of the Netherlands (Koninklijke Bibliotheek, [KB]) and the Nationaal Archief of the Netherlands acknowledged the need for emulation, especially for rendering complex digital objects without affecting their authenticity and integrity. A project was started to investigate the feasibility of emulation by developing and testing an emulator designed for digital preservation purposes. In July 2007 this project ended and delivered a durable x86 component-based computer emulator: Dioscuri, the first modular emulator for digital preservation.